The Thai anesthesia incident monitoring study of perioperative allergic reactions: An analysis of 1996 incidents reports - Lapisatepun W. (2014)
Objectives: Analyze the clinical course, management, outcome, and contributing factors of perioperative allergic reactions in the Thai Anesthesia Incident Monitoring Study (Thai AIMS). Material and Method: A prospective descriptive multicenter study was conducted in 51 hospitals across Thailand. Voluntary, anonymous reports of any adverse or undesirable events during the first 24 hours of anesthesia were sent to the Thai AIMS data management unit. Possible perioperative allergic reactions were extracted and examined independently by three peer reviewers. Results: Forty-three reports of possible perioperative allergic reactions from the 2,537 incidents reported to the Thai AIMS (1.6%) were reviewed. There was a female predominance (1.9:1). The most common features were cutaneous manifestations (93%), arterial hypotension (20.1%), and bronchospasm (11.6%) respectively. The severity grades were 69.8% in grade I, 4.7% in grade II, and 25.6% in grade III. The three most suspected causative agents were neuromuscular blocking agents (39.5%, 30.2%- succinylcholine), antibiotics (27.9%), and opioids (18.6%) respectively. All but one responded well to treatment with complete recovery. One patient suffered acute myocardial infarction and had to stay at the hospital for longer than one week. None had further allergic reaction. Conclusion: Perioperative allergic reactions accounted for 1.6% of anesthetic adverse events. The most common features were cutaneous manifestations. A quarter of these were life-threatening but responded well to treatment. The most common suspected causative agent was succinylcholine.